Socio-cultural manifestation in literary texts - Sujud, Arbaie; Nik Muhamad Affendi, Nik Rafidah; Mohamad, Zulkifli; Atan, Ernawita; Md Zain, Rosnani (Human Resource Management Academic Research Society, 2022)
Language is an important element in the construction of literary works. A good language can educate the community. The same goes the other way around. Therefore, an author needs to choose the language wisely so that the message, lesson, and advice can be well received by the readers. This study aims to classify and analyze the community’s socio-culture found in literary texts. This study utilized textual analysis that using malay folklore. Malay folklore contains many socio-cultural aspects that reflect community life, especially in the use of language. The findings show that the Malay community uses language in literary works to educate the community through continuous learning and mutual respect.